Whey and whey processing - Özdemir, Irem; Ötleş, Semikh; Kabay, Nalan; Yüksel, Mithat (My University, 2016)
Whey is a liquid by-product of the dairy industry produced during the manufacture of cheese and it contains more than half of the solids present in the original whole milk, including whey proteins (20% of the total protein) and most of the lactose, minerals, water-soluble vitamins and minerals. In recent years, whey has been recognized as a major source of nutritional and functional ingredients for the food industry. Commercial whey products include various powders, whey protein concentrates and isolates, and fractionated proteins, such as a-lactalbumin and b-lactoglobulin. The increased interest in separation and fractionation of whey proteins arises from the differences in their functional, biological and nutritional properties. For this reason, the aim of this work is first to put together all the necessary information about whey, its composition, properties, potential usages and describe the common methods of whey processing. Сироватка являє собою рідкий побічний продукт, який утворюється при виробництві сиру. У сироватці міститься більше половини твердих речовин, які є наявними у вихідному незбираному молоці, зокрема білки молочної сироватки (20% від загального білка), більша частина лактози, мінеральні речовини, водорозчинні вітаміни та мінерали. В останні роки, сироватка була визнана основним джерелом поживних речовин та функціональних інгредієнтів серед відходів харчової промисловості. Комерційні продукти, які виробляють із сироватки,  концентрати та ізоляти білків, а також фракціоновані білки, такі як -лактальбумін і -лактоглобулін. Підвищений інтерес до поділу і фракціонування сироваткових білків зумовлений відмінностями їх функціональних, біологічних та поживних властивостей. З цієї причини, метою даної роботи є, передусім, систематизація всієї необхідної інформації щодо сироватки, її складу, властивостей та потенціальних можливостей використання, а також огляд загальних методів переробки сироватки.
Keywords: whey; type of whey; whey composition; whey valorization; whey processing; сироватка; тип сироватки; склад сироватки; ревалоризація; переробка молочної сироватки; сыворотка; тип сыворотки; состав сыворотки; ревалоризация; переработка молочной сыворотки